Human-inspired stable bilateral teleoperation of mobile manipulators. (December 2019) - Santiago, D.D.; Slawinski, E.; Mut, V.
Abstract: This paper presents a novel strategy for delayed bilateral teleoperation of mobile manipulator robots. The strategy is based on the hypothesis that if the slave robot behaves similarly as the operator would do to the same task, the operator's perception of the system states improves, and therefore the performance of the task is better. The proposed scheme allows controlling in simultaneously the mobile platform and the manipulator robot employing a single master device and maintaining the stability of the system against variable and asymmetric communication time delays. Stability guidelines based on Lyapunov–Krasovskii method are provided for the adjustment of the delayed system. Besides, a new control allocation strategy is proposed founded on the study of human movement in a task of navigation–pick and place. Finally, the performance of the proposal is compared with the standard switched control using a real robotic platform. As a result in practice, the proposed scheme is easier and more intuitive for the operator, besides it allows to reduce significantly the time necessary to complete the task. Highlights: This paper proposes a human-inspired strategy for mobile manipulators teleoperation. Allows controlling both base and manipulator with single master device without switching control. A significant reduction in the time to complete a task is achieved in front of a switched scheme. This work contemplates variable and asymmetric time delays and non-passive exogenous sources. An ability proof is provided through Lyapunov–Krasovskii theory.